Design, fabrication and testing of a prototype, thin-vaulted, unreinforced concrete floor. (15th April 2017) - Liew, A.; López, D. López; Van Mele, T.; Block, P.
Highlights: Concept, form-finding, fabrication and testing of a prototype floor system. Floor element that activates arching action to help reduce material. Thin structural thickness of 20 mm with no reinforcing bars. Has accessible internal voids that can be used for services. Experimental study shows service and ultimate load tests. Utilises traditional LVDTs and camera system to measure displacements. Floor element will be used in a research and innovation unit in Switzerland. Abstract: This paper describes the concept, form finding, fabrication and experimental testing of a prototype floor system, derived from principles of shallow arching action, to initiate internal compressive stresses rather than exclusively flexural stresses. This vaulting in a floor system leads to a lightweight structural element, with significant weight savings compared to traditional concrete floor slabs. The form finding process to generate the floor geometry is presented, with a description of the fabrication process, the concrete mix design, material testing and experimental testing. The results from the serviceability and ultimate load testing of the prototype floor are documented in detail. The data showed that the floor unit was both stiff under service load, with maximum vertical deflections less than span/2500, as well as possessing sufficient strength for ultimate loading, carrying 2.5 times the factored design load in a more critical asymmetric loading scenario. A camera setup was used to measure displacements in-line with traditional displacement transducers, to give contour plots of vertical deflections.